1979
DOI: 10.1177/003803857901300203
|View full text |Cite
|
Sign up to set email alerts
|

A Phenomenology of Tourist Experiences

Abstract: Contemporary studies of tourism see the tourist experience as either something essentially spurious and superficial, an extension of an alienated world, or as a serious search for authenticity, an effort to escape from an alienated world. It is argued that neither of these views is universally valid. A more discriminating distinction between five types of tourist experiences is proposed, based on the place and significance of tourist experience in the total world-view of tourists, their relationship to a perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
893
1
121

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,644 publications
(1,034 citation statements)
references
References 10 publications
19
893
1
121
Order By: Relevance
“…In sharp contrast to the notion of living the tourist experience as a way to dissociate from everyday life (Cohen, 1979), the findings revealed a third dimension of value co-creation in connected experiences, which can be described as 'mental detachment' or 'de-territorialisation'. As tourists use their devices to connect to their networks, it was found that they often do so to 'switch to distant places'.…”
Section: ) Mental Detachment and De-territorialisationcontrasting
confidence: 80%
See 1 more Smart Citation
“…In sharp contrast to the notion of living the tourist experience as a way to dissociate from everyday life (Cohen, 1979), the findings revealed a third dimension of value co-creation in connected experiences, which can be described as 'mental detachment' or 'de-territorialisation'. As tourists use their devices to connect to their networks, it was found that they often do so to 'switch to distant places'.…”
Section: ) Mental Detachment and De-territorialisationcontrasting
confidence: 80%
“…However, there appears to be less understanding of how value might be co-destructed by integrating ICTs in order to facilitate such 'connected experiences'. Based on the assumption that travel fulfils the purpose of the reversal of everyday life, escapism and disconnection from the mundane (Cohen, 1979), it is thus of significance to evaluate whether there exist diminishing effects of ICTs resource integration on tourist experiences. By adopting the constructs of value co-creation and value co-destruction as theoretical vehicles, this paper now turns to examine the 'flipside' of technology to understand how value might be destroyed as ICTs become integrated and used.…”
Section: An Era Of Connectednessmentioning
confidence: 99%
“…However, tourist experiences and tourism experiences have been discussed by some authors [1] - [9]. Clawson [1] wrote about recreation experiences; Boorstin [2] discoursed on authenticity in tourist experiences; Cohen [3], [4] studied the phenomenological tourist experiences frames; MacCannell's [5] presented contemporaneous writings on tourist experiences and authenticity. Pearce and Caltabiano [7] further extended consideration of traveller and tourist experiences and authenticity with connections to motivations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Borrie and Birzell [12] presented four ways used to understand tourist and tourism experiences. Those four ways include (1) meanings-based [13], (2) benefits, (3) satisfaction [14], and (4) experience based means [4], [15]. Urry [16], [21] introduced the notion of 'gaze' into considerations of tourist experiences albeit that 'his gazes' were challenged by Perkins and Thorns [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although there has been much interest in authenticity in terms of consumption (e.g. Cohen, 1979), there has been limited attention paid to the desire for experiential authenticity on the part of the producer of the experience, in this case the farm family members. Therefore, within the context of the research, the standpoint of farm family members as actors and producers of farm attractions becomes germane.…”
Section: Experiential Authenticity and Farm-based Attractionsmentioning
confidence: 99%